Clinical Outcomes of Post Placental Intrauterine Contraceptive Device Insertion in Women Delivering by Cesarean Section - Shahzadi Neelum, Javeria Saleem, Sumayya, Saeeda Safi, Noor-Ul-Amina, Mehwish (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Short pregnancy interval after caesarean section increases the risks of morbidity, mortality and surgical interventions. This can be easily avoided by post placental insertion of IUCD during caesarean section. Immediate post placental IUCD insertion is defined as insertion of IUCD within 10 minutes of delivery of the placenta. It is a very promising an appealing approach as patient does not have to come for a separate postpartum visit. Objectives: To determine the outcome (safety, complications, failure and continuation rate) of post placental IUCD insertion during caesarean section. Materials and Methods: Our study was a prospective cross-sectional study, carried out in the Department of Obstetrics and gynecology at Qazi Hussain Ahmad Medical Complex, Nowshera. All the pregnant women willing for post placental intrauterine contraceptive device were included in the study. Women who had postpartum hemorrhage, chorioamnionitis, structurally malformed uterus and fibroid uterus were excluded from the study. Follow up visits were scheduled at one month, 3 months and 6 months. Results: 156 women were included in this study. Majority(35.2%) belonged to 31- 35 years age group. 46.7% of them were illiterate and 30.7% have just primary education. 40.38% of women belonged to low socio-economic group. 26.2% of women were para 4. 26.9% had previous 3 caesarean section. The most common adverse events during follow up of 6months were vaginal discharge, menstrual irregularities and pelvic pain. At the end of 6 months there were 9expulsions, 12 removals and 2 pregnancies with the gross cumulative expulsions, removal, failure and continuation rate of 5.7%, 7.6%, 1.28% and 85.2% respectively. The incidence of undescended strings at the end of 6 months was high (32.4%). Conclusion: Post placental intra uterine Copper T 380 A insertion is a safe, effective and easy reversible method of contraception with low expulsion and high continuation rates. Keywords: Intrauterine device,Intra-cesarean section, Post placental insertion